2010
DOI: 10.1098/rspa.2010.0293
|View full text |Cite
|
Sign up to set email alerts
|

An alternative criterion in heat transfer optimization

Abstract: Entropy generation is recognized as a common measurement of the irreversibility in diverse processes, and entropy generation minimization has thus been used as the criterion for optimizing various heat transfer cases. To examine the validity of such entropy-based irreversibility measurement and its use as the optimization criterion in heat transfer, both the conserved and non-conservative quantities during a heat transfer process are analysed. A couple of irreversibility measurements, including the newly defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 23 publications
1
47
1
1
Order By: Relevance
“…This loss or dissipation of the energy can be used as the measurement of irreversibility in these transport processes. However, an irreversible heat transfer process seems to have its own particularity, for the heat energy always remains constant during transfer and it doesn't appear to be readily clear what the non-conserved quantity is in a heat transfer process (Chen et al, 2011). Based on the analogy between electrical and heat conductions, Guo et al (2007) made a comparison between electrical conduction and heat conduction as shown in table 1.…”
Section: The Origin Of Entransymentioning
confidence: 99%
See 3 more Smart Citations
“…This loss or dissipation of the energy can be used as the measurement of irreversibility in these transport processes. However, an irreversible heat transfer process seems to have its own particularity, for the heat energy always remains constant during transfer and it doesn't appear to be readily clear what the non-conserved quantity is in a heat transfer process (Chen et al, 2011). Based on the analogy between electrical and heat conductions, Guo et al (2007) made a comparison between electrical conduction and heat conduction as shown in table 1.…”
Section: The Origin Of Entransymentioning
confidence: 99%
“…1. Two-dimensional heat conduction with a uniformly distributed internal heat source (Chen et al, 2011) According to the new extremum principle based on entransy dissipation, for this volumepoint heat conduction problem, the optimization objective is to minimize the volumeaverage temperature, the optimization criterion is the minimum entransy dissipation, the optimization variable is the distribution of the HTCM, and the constraints is the fixed amount of the HTCM, i.e., ( )…”
Section: Application To a Two-dimensional Volume-point Heat Conductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Guo et al proposed the entransy dissipation extremum principle to optimize the processes of heat conduction [11][12][13][14][15], heat convection [16,17], and thermal radiation [18].…”
mentioning
confidence: 99%